Correlation Between Family Support and Depression Among Pre-Elderly Individuals with HIV in Jakarta - Gracella Tanjaya; Surilena Surilena; Nicholas Hardi; Eva Suryani (Fakultas Ilmu Keperawatan Universitas Indonesia, 2025)
Depression among pre-elderly with human immunodeficiency virus (HIV) can significantly impact their quality of life. Family is often the primary source of support for this demographic and is recognized as a protective factor against depression. Therefore, identifying protective factors against depression is essential for promoting healthy aging among pre-elderly with HIV. This study aimed to determine the correlation between family support and depression among pre-elderly with HIV in Jakarta. A total of 120 pre-elderly with HIV from the Indonesia AIDS Coalition who were receiving HIV care at health centers across Jakarta participated in this cross-sectional study. The participants were recruited using convenience sampling. Data collection involved demographic questions, a family support questionnaire, and the Depression Anxiety Stress Scales 21 (DASS-21). The analysis comprised univariate and bivariate analyses. The univariate analysis described the characteristics, family support, and depression levels, while the bivariate analysis assessed the correlation between the variables using the Spearman test. The results indicated that pre-elderly with HIV primarily received support from siblings and spouses. The participants reported low family support (median 25.00) and mild depressive symptoms (median 8.00). A significant moderate negative correlation was found between family support and depression in this population (r = -0.344). This study suggests that enhancing family support for pre-elderly with HIV can help reduce depression. Consequently, there is a critical need for healthcare providers to engage families in the treatment of pre-elderly with HIV to mitigate depression and promote healthier aging. Keywords: depression, family support, HIV, pre-elderly Abstrak Korelasi antara Dukungan Keluarga dan Depresi: Sebuah Studi pada Pra-lansia dengan HIV di Jakarta. Depresi pada pra-lansia dengan HIV dapat memengaruhi kualitas hidupnya. Keluarga dapat menjadi sumber dukungan utama bagi pra-lansia dan diketahui merupakan faktor protektif terhadap depresi. Maka dari itu, perlu dilakukan identifikasi terkait faktor protektif terhadap depresi agar pra-lansia dengan HIV dapat menua dengan baik. Penelitian ini bertujuan untuk melihat korelasi antara dukungan keluarga dengan depresi pada pra-lansia dengan HIV di Jakarta. Penelitian cross-sectional ini diikuti oleh 120 pra-lansia dengan HIV yang tergabung di Indonesia AIDS Coalition dan menerima pengobatan HIV di layanan kesehatan Jakarta dengan metode convenience sampling. Digunakan kuesioner karakteristik, kuesioner dukungan keluarga, dan DASS-21. Analisis data terdiri atas analisis univariat untuk melihat gambaran karakteristik, dukungan keluarga, dan depresi, sedangkan analisis bivariat untuk menguji korelasi menggunakan Spearman test. Pra-lansia dengan HIV menerima dukungan keluarga utamanya dari saudara kandung dan pasangan. Didapatkan bahwa partisipan mendapatkan dukungan keluarga yang relatif rendah (median 25,00) dan tingkat depresi yang ringan (median 8,00). Terdapat korelasi negatif yang signifikan dengan tingkat sedang antara dukungan keluarga dengan depresi pada pra-lansia dengan HIV di Jakarta (r = -0,344). Studi ini menunjukkan bahwa peningkatan dukungan keluarga pada pra-lansia dengan HIV dapat membantu menurunkan depresi. Dengan demikian, menjadi penting bagi tenaga kesehatan untuk melibatkan peran keluarga dalam tatalaksana pra-lansia dengan HIV. Melibatkan keluarga dalam perawatan pra-lansia dengan HIV perlu mendapat perhatian khusus untuk mengurangi depresi dan mendukung proses penuaan yang lebih sehat. Kata Kunci: depresi, dukungan keluarga, HIV, pra-lansia